A Robust Model System for Retinal Hypoxia: Live Imaging of Calcium Dynamics and Gene Expression Studies in Primary Human Mixed Retinal Culture - Shahulhameed, Shahna; Swain, Sarpras; Jana, Soumya; Chhablani, Jay; Ali, Mohammad Javed; Pappuru, Rajeev R.; Tyagi, Mudit; Vishwakarma, Sushma; Sailaja, Nanda; Chakrabarti, Subhabrata; Giri, Lopamudra; Kaur, Inderjeet (Frontiers in Neuroscience, 2020)
The detailed mechanisms underlying oxidative stress leading to neuroinflammation and neurodegeneration in retinal vascular conditions including diabetic retinopathy, retinopathy of prematurity etc. remains largely unexplored mainly due to lack suitable disease models that can simulate the inherent neuron-glia interactions in human retina. Specifically, establishment of a mixed retinal culture containing both neuron and glial cell types remains a challenge due to different conditions required for their optimal growth and differentiation. Here, we establish a novel primary mixed retinal culture (MRC) model system containing neurons, astrocytes, Müller glia and microglia from human donor retina that can be used to study the neuromodulatory effects of glial cells under the stress. The cell characterization based on immunostaining with individual cell types specific markers and their presence in close vicinity to each other further underscores their utility for studying their crosstalk. To the best of our knowledge, this is the first instance of an in vitro model obtained from human donor retina containing four major cell types. Next, we induce hypoxic stress to MRC to investigate if hypoxia activated neuro-glia modulates altered gene expression for inflammatory, apoptotic andangiogenic markers and Ca2+ transients by live cell imaging. Further, we performed k-means clustering of the Ca2+ responses to identify the modification of clustering pattern in stressed condition. Finally, we provide the evidence that the altered Ca2+ transient correlates to differential expression of genes shown to be involved in neuro-inflammation, angiogenesis and neurodegeneration under the hypoxic conditions as seen earlier in human cell lines and animal models of diabetic retinopathy. The major features of the hypoxic conditions in the proposed human MRC model included:increase in microglia activity, chemokine and cytokine expression and percentage of cells having higher amplitude and frequency of Ca2+ transients. Thus, the proposed experimental system can potentially serve as an ideal in vitro model for studying the neuroinflammatory and neurodegenerative changes in retina and identifying newer drug targets.